Dopaminergic Modulation of Prospective Memory in Parkinson’s Disease - Costa, Alberto (Behav Neurol, 2008)
Growing interest is present in literature on the study of prospective memory functioning in Parkinson’s disease (PD). Current data indicate that prospective memory may be impaired in PD and a relationship with general executive dysfunctioning has been suggested. However, although the dopamine dependency of cognitive dysfunction in PD has been widely investigated, poor is known on the dopaminergic modulation of PM. In the present study we explored the effect of acute administration of levodopa on the performance of a PD sample (n = 20) in a time-based prospective memory task. PD patients were evaluated in the morning after a 12-hour therapy wash-out in two experimental conditions: i) after levodopa assumption (“on”); (ii) without drug administration (“off”). The experimental task required to execute three uncorrelated actions after 10' for three consecutive trials. Distinct scores for the spontaneous recall of the intention to perform the actions (prospective component) and for the correct execution of the actions (retrospective component) have been computed. Results showed that in the “off”condition PD patients were selectively impaired on the prospective component of the task. However, L-dopa administration significantly improved PD patients’ performance actually restoring the prospective memory deficit. These results support a critical role of dopaminergic modulation in prospective memory processes in PD patients, possibly through the replacement of dopamine levels in fronto-striatal pathways.